Pengaruh Pajak, Tunneling Incentive dan Mekanisme Bonus Terhadap Keputusan Transfer Pricing - Mispiyanti Mispiyanti (Universitas Muhammadiyah Yogyakarta, Indonesia, 2015)
The aim of the research is to find empirical effidence of tax, tunneling incentive and bonus mecahnism toward transfer pricing decision taken by manufacturing companies listed in Indonesia Stock Exchange. The research population are manufacturing companies listed in Indonesia Stock Exchange arround 2010 to 2013. The samples were taken using purposive sampling method. The research results show that tax and bonus mechanism do not have effect toward companies’ transfer pricing decision. While, tunneling incentive has effect toward companies’transfer pricing decision.